(untitled) (Journal of Hama University, 2019)
This research aimed at investigating the aesthetics of style in Zuhair Ibn Abi Sulma’s classical poem (Muallaqa). It started with a brief introduction about the concept of style; then, it studied the pictorial style. That is, it sets out to analyze a number of similes and metaphorical images so as to detect the aesthetics of this style. Then, it touched on a number of advancing and delaying topics in an attempt to illustrate its aesthetic features. Afterwards, it choses a number of antithesis points which were so clear in the poetics of the poem. Then, it sought to examine the aesthetics of the narrative style by studying the story of the riding camels and the story of the conflict between good and evil. The research ended with the findings it had reached